Identification of morphological differences between avian influenza A viruses grown in chicken and duck cells - Al-Mubarak, Firas; Daly, Janet M.; Christie, Denise; Fountain, Donna; Dunham, Stephen P. (Elsevier, 2015)
Although wild ducks are considered to be the major reservoirs for most influenza A virus subtypes, they are typically resistant to the effects of the infection. In contrast, certain influenza viruses may be highly pathogenic in other avian hosts such as chickens and turkeys, causing severe illness and death. Following in vitro infection of chicken and duck embryo fibroblasts (CEF and DEF) with low pathogenic avian influenza (LPAI) viruses, duck cells die more rapidly and produce fewer infectious virions than chicken cells. In the current study, the morphology of viruses produced from CEF and DEF cells infected with low pathogenic avian H2N3 was examined. Transmission electron microscopy showed that viruses budding from duck cells were elongated, while chicken cells produced mostly spherical virions; similar differences were observed in viral supernatants. Sequencing of the influenza genome of chicken- and duck-derived H2N3 LPAI revealed no differences, implicating host cell determinants as responsible for differences in virus morphology. Both DEF and CEF cells produced filamentous virions of equine H3N8 (where virus morphology is determined by the matrix gene). DEF cells produced filamentous or short filament virions of equine H3N8 and avian H2N3, respectively, even after actin disruption with cytochalasin D. These findings suggest that cellular factors other than actin are responsible for the formation of filamentous virions in DEF cells. The formation of elongated virions in duck cells may account for the reduced number of infectious virions produced and could have implications for virus transmission or maintenance in the reservoir host.